Chapter 26 Developing mediation competence through translation - Maria González-Davies (Taylor & Francis, 2020)
"The Routledge Handbook of Translation and Education will present the state of the art of the place and role of translation in educational contexts worldwide. It lays a sound foundation for the future interdisciplinary cooperation between Translation Studies and Educational Linguistics. By adopting a transdisciplinary perspective, the handbook will bring together the various fields of scholarly enquiry and practice that make a valuable contribution to enlarging the notion of translation and diversifying its uses in education. Each contribution provides an overview of the historical background to a given educational setting. Focusing on current research approaches and empirical findings, this volume outlines the development of pedagogical approaches, methods, assessment and curriculum design. The handbook also examines examples of pedagogies that integrate translation in the curriculum, the teaching method's approach, design and procedure as well as assessment. Based on a multilingual and applied-oriented approach, the handbook is essential reading for postgraduate students, researchers and advanced undergraduate students of Translation Studies, and educationalists and educators in the 21st century post-global era."